A PROSPECTIVE STUDY COMPARING CONCURRENT CHEMORADIATION WITH OR WITHOUT GEFITINIB IN TREATMENT OF LOCALLY ADVANCED HEAD AND NECK CARCINOMA - BANERJEE, BISWARUP; DE, SUMITAVA; BISWAS, LINKON; MANDAL, SRIKRISHNA (Asian Journal of Pharmaceutical and Clinical Research, 2022)
ABSTRACT BACKGROUND-Concurrent chemoradiotherapy (CTRT) is now an acceptable definitive therapy for locally advanced head and neck carcinomas. But, multiple studies revealed that addition of anti-EGFR agent with CTRT improves the loco-regional response at a cost of higher but acceptable toxicity. Our study aimed at assessing CTRT with or without Gefitinib in terms of treatment response and acute toxicity profile. MATERIALS AND METHODS- Patients with Locally advanced, non-metastatic, squamous cell carcinoma of Head-neck were randomised in two groups-the control group received external beam radiotherapy 66Gy/33 fractions/6.5 weeks along with concurrent injection Cisplatin at the dose of 100mg/m2 on day 1, 22, and 43 during radiation and the study group received concurrent chemoradiotherapy along with Tab Gefitinib-250 mg during the duration of radiotherapy. Response assessment was done after completion of treatment and all patients were followed up for treatment related acute toxicity during the course of treatment and then at every month for at least 6 months. RESULTS- 46.66% of study arm (CTRT+Gefitinib) patients showed complete response and Overall response was 79%. In control arm (CTRT alone), there was 51.6% complete response and Overall response was 77%, though difference was statistically not significant (p value 0.84). Although statistically not significant, Gefitinib containing arm had numerically higher hematological, gastro-intestinal toxicity and weight loss. CONCLUSION- Gefitinib along with chemoradiation showed numerically higher overall response (complete response + partial response) and comparable acute toxicity profile in comparison to chemoradiation alone.